Using a healing robot for the scientific study of Shirodhara. - Uebaba, K. (IEEE Engineering in medicine and biology magazine)
One of the critical problems in the study of physiotherapy of Oriental medicine is not being able to use the same reproducible stimulation, especially in Ayurvedic oil treatments. To address this problem, we developed a healing robot which conducts shirodhara (an oil treatment) in a computerized reproducible manner. The physio-psychological changes during taila dhara conducted by the healing robot and an estimated psychological experiences during taila dhara by psychometric studies of anxiety and altered states of consciousness (ASC) were studied. The physiological changes of the practitioners themselves were checked. Sixteen healthy adult females (ages 21-56, 33 ± 9 years) signed informed consent and participated in this study. During shirodhara the monitoring items for the subjects were: blood pressure and intermittent blood pressure, electrocardiogram (ECG) R-R intervals, expired gas analysis, impedance cardiography and electroencephalogram (EEG). The single EEG (C3 lead) of the technician was recorded at the same time, and respiratory movement of the chests of both subject and technician were also recorded. In the active studies, shirodhara was performed by a machine with a pumping and heating system. The subject's feelings during shirodhara showed deep restfulness with less anxiety - as if the subjects were between the sleep and awake states. Shirodhara induced bradycardia and the relative suppression of LF/HF power spectrum density, which indicated lowered sympathetic tone. Expired gas analysis showed a decreased tidal volume and CO2 excretion. The EEG showed the slowing of the α wave, an increase in α and θ activity and an increase in right-left coherence. These metabolic, ECG, and EEG findings support the reported experiences of relaxed and low metabolic states during shirodhara. Physiological changes during shirodhara were similar to those of meditation, including α-wave dominance in the frontal area and a decrease in heart rate and CO2 excretion. These findings indicated a change in the function of the frontal lobe, limbic system, brain stem, and autonomic nervous system. On the other hand, the EEGs of the technicians of the manual shirodhara showed an increase in their stressful condit- ion, which may also justify the utility of the healing robot as an assistant for the technicians.